Prevalence of Academic Procrastination among Students of Faculty of Psychology and Educational Science, Kabul University - ayubi, Bezhan; Mohammadi, Omulbanin Moradi (Journal of Social Sciences - Kabul University, 2023)
Academic procrastination is a common problem among university students. This study aimed to assess the prevalence of academic procrastination among students of Faculty of Psychology and Educational Science. A cross-sectional design was used and 232 students selected randomly as sample of the study. The prevalence of academic procrastination was assessed by Farsi-Dari version of Solomon and Rothblum academic procrastination questionnaire (1984) was used to collect the necessary data. Descriptive and inferential statistics were applied using statistical package for social sciences (SPSS) version 21 for data analysis. The results showed that level of procrastination is higher (59.36) than average (50). Furthermore, this research indicated that gender, interest in field of study and age has no influence on procrastination. Authorities and lecturers of Faculty of Psychology and Educational Science must design the appropriate programs to decrease the level of procrastination in the faculty. It is suggested that the same research should be conducted at university level to obtain a clear picture of the problem.